Research on the Physics of Cancer : A Global Perspective - Gerstman, Bernard S (Singapore : World Scientific Publishing Co. Pte Ltd., 2016)
"There is something special about cancer compared to other diseases. It is a horrific disease that has defied attempts to find a reliable cure. Life spans after diagnosis have increased, but the mortality rate has remained about the same even after 40 years of extensive research. Cancer provides a major scientific challenge. Tumors evolve and spread in response to internal and external factors that involve feed-back mechanisms and non-linear behavior. In recent years, physicists have become involved in studying cancer, with the ultimate aim of finding a cure. Physicists approach a problem with unique experimental, theoretical, and computational skills and perspectives. This book will be comprised of chapters written by physicists from all over the world who perform research on cancer. They will describe their research and summarize their results."--Provided by the publisher.
Includes bibliographical references and index.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Cancer cells -- Mechanical properties; Cancer -- Research; Electronic books